(Re)Placing the Terengganu Peranakan Chinese as “Mek Awang”: Making Chinatown and Heritagising the Peranakan Identities in Kuala Terengganu - Loo Hong Chuang; Pue Giok Hun; Ong Puay Liu (Kajian Malaysia, 2021)
In 2017, the Terengganu Chinese Peranakan Association (TCPA) withdrew its participation in the 4th Annual Terengganu Peranakan Festival (TPF) organised by the Terengganu Chinese Chamber of Commerce and Industry (TCCCI) because of a dispute over the combined term “Mek Awang”. To TCPA members, Mek Awang is a derogatory term, which the Malays used to refer to someone as being “soft”, effeminate, or a cross-dresser. However, TCCCI has appropriated the term Mek Awang and used it as a brand name to promote the festival, and to highlight the “uniqueness” of the Terengganu Peranakan Chinese community. This case is an example of how local cultural terms or practices have been readapted to suit tourism interests. Tourism is often accused of reinventing culture for capital ventures. Consequently, many academics and social critics have come to regard official national heritage sites and heritage tourism with scepticism and disdain. Combining ethnographic data from our in-depth interviews with the Terengganu Peranakan Chinese and our participant observation during the festival, we argue that the dispute over Mek Awang is not only a simple change in reference, but is also an indication of a deeper contemporary global process that affects ethnic minorities and their identities. We conclude that various attempts to commodify the peranakan experiences and culture in Terengganu as well as the intention to place the peranakan as a marketable heritage in Chinatown can be interpreted as attempts to replace a heterogeneous community with a homogeneous, uniform, genetic and identifiable ethnic category with a Peranakan1 (with capital “P”) identity.